Use of a Vessel Sealant Device for Cystic Duct Ligation in the Dog. Issue 8 (11th September 2014) - Marvel, Sarah; Monnet, Eric
<x xml:space="preserve">Abstract</x> Objective To compare a vessel sealant device to hemostatic clips for cystic duct ligation in a canine cadaveric model. Study Design Experimental. Methods Hepatobiliary systems were collected from normal dogs. A microtip pressure transducer was inserted into the common bile duct and a 20–24 g intravenous catheter was placed in a hepatic duct. The cystic duct was ligated with 1 of 3 techniques: vessel sealant device (VSD), 10 mm medium Endoclips™, or 10 mm large Endoclips™ with 6 specimens in each group. Methylene blue was infused until failure, which was recorded as seal/clip failure or retrograde movement of methylene blue into the liver. Results Mean failure pressure of the medium endoclip group was significantly lower than the large endoclip group (P = .014). There was no difference between the failure pressure of the VSD group and the medium and large endoclip groups (P = .097, P = .34, respectively). Failure by leakage at the cut surface of the cystic duct occurred in 2 specimens in the medium endoclip group while all others failed by retrograde flow of the methylene blue through the hepatic ducts. Conclusions The vessel sealant device appears comparable to large endoclips for closure of the cystic duct in an acute cadaveric model, while medium endoclips may not fully compress or span the diameter of a cystic duct in large breed dogs and leak at lower pressures.